Involusi politik : esei-esei transisi Indonesia - Lay, Cornelis, 1959- (Yogyakarta : Program S2 Politik Lokal dan Otonomi Daerah Universitas Gadjah Mada [dan] Jurusan Ilmu Pemerintahan Fisipol UGM, 2006)
Essays on sociopolitical conditions in Indonesia after the New Order era.
Includes bibliographical references (p. 291-302) and index.
Keywords: Political corruption -- Indonesia; Indonesia -- Politics and government -- 1998-